The Politics of Police Governance: Scottish Police Reform, Localism, and Epistocracy - Malik, Ali (Policy Press, 2024)
This book analyses police reform in Scotland, demonstrating the key role experts can play in strengthening democratic accountability of the police to the communities they serve.